Hemangioma e hemangiossarcoma cutâneo em pequenos animais: revisão de literatura - Regatieri, Nicolas Decoló (Universidade Estadual Paulista (Unesp), 2022)
Hemangiomas and hemangiosarcomas (HSA) are mesenchymal neoplasia that have their origin on vascular endothelium. Hemangiomas are benign tumors, while HSA are the malignant form frequently causing hemorrhage, death and euthanasia in small animals. The visceral form of the desease frequently metastasize into other tissues, but the same doesn’t occur in the cutaneous form. Cutaneous hemangiosarcoma are more frequent in dogs, mainly of breeds like pitbull, dalmatian, boxer and whippet, but also affects cats, less frequently, with no difference between breeds. Apparently there is no sexual predisposition for the occurence of this neoplasia, but there is for neutering. There is an apparent relation between solar radiation exposure and developing of hemangiomas and hemangiosarcomas, with short hair and light skin animals most frequently affected. The abdominal region is most frequently compromised in dogs and the head in cats. The treatment of choice for cutaneous hemangiosarcomas is the excision of the neoplasia. Even thou surgical excision is the method of choice, other possible adjuvant and palliative techniques have been described. Histopathologic exam gives the definitive diagnosis, so a sample from the primary tumor or metastasis is necessary. Before tumor excision, chemotherapy or other therapeutic protocol, patient stabilization is necessary

Hemangiomas e hemangiossarcomas (HSA) são neoplasias mesenquimais que tem sua origem no endotélio vascular. Hemangiomas são tumores benignos, enquanto HSA são malignos e frequentemente causa de hemorragias, morte e eutanásia em pequenos animais. A forma visceral da doença frequentemente metastatiza para outros tecidos, entretanto o mesmo não ocorre na forma cutânea. Hemangiossarcoma cutâneo é mais frequente em cães, principalmente de raças como pitbull, dálmata, boxer e whippet, mas também acometem gatos, em menor frequência e sem diferença entre raças. Aparentemente não há predisposição sexual para a ocorrência destas neoplasias, porém há relação com a castração do animal. Há uma associação entre a exposição à radiação solar e o desenvolvimento de hemangiomas ou hemangiossarcomas, sendo animais com pelo curto e pele clara os mais acometidos. A região abdominal é frequentemente afetada em cães e a cabeça em gatos. O tratamento de escolha para hemangiossarcomas cutâneos é a excisão cirúrgica da neoplasia, apesar de outras técnicas adjuvantes e paliativas já serem descritas. O diagnóstico é realizado pelo exame histopatológico e, portanto, é necessária amostra do tumor primário ou metástase. Previamente a excisão do tumor, quimioterapia ou demais protocolos terapêuticos, é necessário estabilização do paciente.
Cutaneous hemangioma and hemangiossarcoma in small animals: literature review
Keywords: Cat; Dog; Skin; Oncology; Neoplasia; Gato; Cão; Pele; Oncologia; Neoplasia